Causal Effects of Inclusion on Postsecondary Education Outcomes of Individuals With High-Incidence Disabilities. (March 2015) - Rojewski, Jay W.; Lee, In Heok; Gregg, Noel
Using data from the National Longitudinal Transition Study–2 results of a propensity score analysis revealed significant causal effects for inclusive placement in high school on postsecondary education outcomes for adolescents with learning disabilities or emotional-behavior disorders 2 years after high school completion. Students earning 80% or more of their academic credits in general education settings (inclusive placement) were twice as likely to enroll and persist in postsecondary education when compared with students receiving fewer credits in inclusive classroom settings. These findings extend results of past descriptive and correlational studies by detecting a direct causal link between inclusion and postsecondary education.